Leadership competencies: Tools for the promotion of quality in health care - Veloso , John Wesley Nascimento; Machado , José Lúcio Martins; Ortiz , Sandra Regina Mota; Santos , Alba Lucia Dias dos (Seven Editora, 2023)
At this moment 'shared leadership' is in discussion. This means to delegate more autonomy to those who work on all levels of organizations as well as to give them the chance to become individuals and also citizens capable of changing things and assuming reponsibilities in order to direct their actions in search of the already planned objectivities. The structure of the old administration has to make room to new ones which should be more flexible, wider and more decentralized, thus creating autonomy, pro-activity, and conditions for every single one to assume leadership. The hospital is not an outsider in this process and goes also through a renewed form of thinking and planning. In this sense, both Medicine and the other multidisciplinary areas of health has assumed different roles within its care activities linked to the patient until health management, thinking not only about managing with leadership skills, but also interacting with new times and methods, becoming audacious from mechanisms like a lot of attention and emotion, intelligence and self-development to break paradigms of a professional profile. This study sought to analyze the Leadership Competencies as tools for the promotion of quality in health care, based on Explanatory Research and meta-analysis in a hospital, with 37 graduated and specialized health professionals. DOI:https://doi.org/10.56238/globalhealthprespesc-044